Tumor carcinoide y apendicitis aguda. - Vilorio Barrera, Pedro; Salgado Suárez, Daniel; Sanz Reyes, Andrés; Fernández- Britto Rodríguez, José E.; Wong Navarro, Roberto (Revista Cubana de Pediatría, 2023)
Niña de 8 años portadora de una apendicitis agua y un turmor carcinoide del apéndice.